Validity, reliability and applicability of Portuguese versions of sedation-agitation scales among critically ill patients - Antonio Paulo Nassar Junior; Ruy Camargo Pires Neto; Walquiria Barcelos de Figueiredo; Marcelo Park (São Paulo Medical Journal)
CONTEXT AND OBJECTIVE: Sedation scales are used to guide sedation protocols in intensive care units (ICUs). However, no sedation scale in Portuguese has ever been evaluated. The aim of this study was to evaluate the validity and reliability of Portuguese translations of four sedation-agitation scales, among critically ill patients: Glasgow Coma Score, Ramsay, Richmond Agitation-Sedation Scale (RASS) and Sedation-Agitation Scale (SAS). DESIGN AND SETTING: Validation study in two mixed ICUs of a university hospital. METHODS: All scales were applied to 29 patients by four different critical care team members (nurse, physiotherapist, senior critical care physician and critical care resident). We tested each scale for interrater reliability and for validity, by correlations between them. Interrater agreement was measured using weighted kappa (k) and correlations used Spearman's test. RESULTS: 136 observations were made on 29 patients. All scales had at least substantial agreement (weighted k 0.68-0.90). RASS (weighted k 0.82-0.87) and SAS (weighted k 0.83-0.90) had the best agreement. All scales had a good and significant correlation with each other. CONCLUSIONS: All scales demonstrated good interrater reliability and were comparable. RASS and SAS showed the best correlations and the best agreement results in all professional categories. All these characteristics make RASS and SAS good scales for use at the bedside, to evaluate sedation-agitation among critically ill patients in terms of validity, reliability and applicability.